Diffusion MRI - Johansen-Berg, H; Behrens, T (Elsevier, 2009)
Diffusion imaging is a non-invasive MR technique that is now being used in novel ways to study aspects of white matter anatomy that could never before be investigated in the living brain. The technique therefore has enormous potential for addressing novel research questions in both basic and clinical neuroscience. This book aims to cover the field of diffusion imaging from the fundamental theory to its most cutting-edge applications. It contains sufficient detail to be a reference book for medical physicists, but will also cover fundamental aspects of experimental design and example applications that will be of interest to clinical and basic neuroscientists. Importantly, the book presents diffusion imaging in the context of well-established, classical experimental techniques, so that readers will be able to assess the scope and limitations of the new imaging technology with respect to techniques available previously. Each section includes chapters on methodology (with the more advanced, mathematical material included in appendices for the interested reader), validation of the imaging technology, and application of diffusion imaging to the study of variation and development of normal brain anatomy, and disruption to the white matter in neurological disease or psychiatric disorder. The aim of the book is to become an essential reference text for scientists designing or interpreting diffusion MR experiments. Key Features - The first comprehensive reference on a powerful technique in Brain Imaging - Contributions from the key scientists in the field, including pioneers of the field Peter BAsser (NIH), Susumu Mori (Johns Hopkins University), and others - Describes the physical foundations, methods for quantitative analysis, and how the technique is applied to the cutting edge analysis of connections in the brain - Full color throughout, carefully edited for clarity in style. © 2009 Elsevier Inc. All rights reserved.